2020
DOI: 10.1161/circulationaha.120.050645
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Ticagrelor and Clopidogrel in Elderly Patients With an Acute Coronary Syndrome

Abstract: Background: The comparative efficacy and safety of ticagrelor vs. clopidogrel in older myocardial infarction (MI) patients has received limited study. Methods: We performed an observational analysis of all patients ≥80 years (n=14005) who were discharged alive with aspirin combined with either clopidogrel (60.2%) or ticagrelor (39.8%) after a MI between 2010 and 2017 registered in the national registry Swedish Web-System for Enhancement and Development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 27 publications
2
69
3
2
Order By: Relevance
“…A Swedish based observational study supported the effectiveness of ticagrelor; 174 however, more recent studies have questioned the effectiveness of ticagrelor when used in clinical practice. [175][176][177][178][179] This is clearly relevant for the results of our case study since effectiveness estimates are central to the value that ticagrelor provide. Paper 4 investigates this particular issue.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A Swedish based observational study supported the effectiveness of ticagrelor; 174 however, more recent studies have questioned the effectiveness of ticagrelor when used in clinical practice. [175][176][177][178][179] This is clearly relevant for the results of our case study since effectiveness estimates are central to the value that ticagrelor provide. Paper 4 investigates this particular issue.…”
Section: Discussionmentioning
confidence: 94%
“…160,163 However, observational studies on ticagrelor use in clinical practice has produced varying and conflicting evidence on ticagrelor effectiveness. [175][176][177][178][179][181][182][183][184] Some studies have found positive effects from ticagrelor when used in clinical practice, including a study by Sahlén et al (2016) who analysed data collected as part of Swedish routine clinical practice. 174 Other studies have found zero and even negative effects of ticagrelor use in clinical practice, including a recent study by Szummer et al (2020) who found an increased risk of mortality associated with ticagrelor in patients above 80 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Swedish Web-system for Enhancement and Development of Evidencebased care in Heart disease Evaluated According to Recommended Therapies (SWEDEHEART) records, it was reported that at the age of 80 years and above ticagrelor decreased ischemic events and stroke rates compared to clopidogrel, but significantly increased death and bleeding complications. However, it has been emphasized that there is a need for randomized studies, especially in elderly patients [11]. In the light of these data, it would be reasonable to routinely evaluate the application of clopidogrel de-escalation during the in-hospital stay 24 hours after the index event without such adverse events, especially in elderly patients who are prone to complications.…”
Section: Discussionmentioning
confidence: 99%
“…Im 1-Jahres-Verlauf hatten die Patienten des Clopidogrel-Arms weniger Blutungskomplikationen ohne eine Zunahme des kombinierten Endpunkts von Gesamtsterblichkeit, Myokardinfarkt, Schlaganfall und Blutung. Die Ergebnisse der POPular-AGE-Studie werden durch eine Subanalyse des SWEDEHEART(Swedish Websystem for Enhancement and Development of Evidence-based care in Heart disease Evaluated According to Recommended Therapies)-Registers bestätigt [20]. In dieser Analyse war Ticagrelor bei alten Patienten (≥80 Jahre) im Vergleich zu Clopidogrel mit einem höheren Risiko von Blutungen und einer erhöhten Sterblichkeit verbunden.…”
Section: Introductionunclassified